A novel 3D pillar-layered metal-organic framework: Pore-size-dependent catalytic activity and CO2/N2 affinity. (1st April 2020) - Ghasempour, Hosein; Azhdari Tehrani, Alireza; Morsali, Ali; Wang, Jun; Junk, Peter C.
Graphical abstract: Effects of pillaring linkers length on the size-dependent catalytic activity of two isoreticular metal–organic frameworks toward the aldol-type condensation reaction between malononitrile and α, β-unsaturated carbonyl compound. The result shows that the selectively of TMU-52 toward different substrate was significantly higher than TMU-25. Abstract: The structure–activity relationship plays the main role in the applicability of Metal-organic Frameworks (MOFs) in different areas including catalysis. Regarding to this herein a novel pillar-layered MOF (TMU-52) that is isostructural to our recently reported TMU-25 is introduced. The structure of this framework was analyzed using X-ray crystallography, FT-IR spectroscopy, Thermogravimetric and elemental analyses. According to the similar organic and inorganic backbone, a comparative study was done on catalytic manner of TMU-25 and TMU-52 toward in aldol-type condensation reaction. TMU-52 was designed through replacing the biphenyl core in the pillar linker of TMU-25 with phenyl group as a better candidate heterogeneous catalysis. The selectivity of the TMU-52 was higher owing to its narrower channels. CO2 /N2 affinity of these structures was also investigated.